(untitled) (Research, Society and Development, 2021)
Breast cancer is a disease caused by the disordered multiplication of breast cells. This process generates abnormal cells that multiply, forming a tumor. An integrative literature review was carried out with the aim of characterizing the research produced with the theme drug interaction in patients with breast cancer. The bibliographic survey covered studies carried out in Brazil, with no restrictions on the year of publication of the works, in scientific journals and that were adequate to the theme proposed for the work, in the period from August to September 2021 in the PubMed, SCIELO and VHL, using the following descriptors: “Drug Interactions”, “breast cancer” and “Brazil”. After analysis, 9 articles were identified that made up the study sample. The results show that in most of the articles analyzed, drug interaction in cancer patients is presented as the main problem related to drugs. In all, the importance of monitoring prescriptions and working together with the multidisciplinary team is perceived, with the pharmacist being fundamental for the care of patients with breast cancer.